Antiproton impact ionization of hydrogen atom: Differential cross sections computed by Coulomb wave function discrete variable representation method - Gombosuren, Zorigt; Chuluunbaatar, Aldarmaa; Lochin, Khenmedekh; Oidov, Lkhagva; Erdenebayar, Khatanbold (Journal of Applied Science and Engineering A, 2022)
Our aim is using the Coulomb wave function discrete variable representation method (CWDVR) for the calculation of collision problem in first time. Nonrelativistic collision of antiproton with hydrogen atom is described by solving the time-dependent Schrodinger equation numerically. Two collision amplitudes are used for calculation of the differential cross sections, one of them corresponds to impact parameter of the projectile while other one is determined by projectile momentum transfer and found by Fourier transform of the first one. The ionization amplitude calculated by projecting of the wave function onto continuum wave function of the ejected electron. The differential cross sections calculated depending on projectile impact energy, scattering angle and electron ejection energy and angles, which is a result that can be measured experimentally. Our results are in good agreement with the relativistic calculation results.